PERANCANGAN MODEL BISNIS BIDANG KOSMETIK RIAS PADA USAHA RINTISAN PHEBEE LIP BALM MENGGUNAKAN BUSINESS MODEL CANVAS - Indriantini, Elni Hazar; Purnomo, Dwi; Mardawati, Efri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 2 (2019): Juni, 2019)
The design of business models at startup companies engaged in the field of technology is needed, this aims to introduce the values of the company and product on the consumer and the public so that have added value and the marketability can compete. This research aims to develop a business model for the validation of the Phebee Lip balm using a business model canvas. The research was done by designing business models in accordance with the literature and case studies are needed, then the business model validated to respondents contained on each column business model canvas. The results suggested that the company is Phebee Lip balm must continue to make improvements to introduce the values of products to consumers and communities, namely local lip balm products, natural lip balm is made from natural ingredients and it is safe to use and has no side effects. Keywords : Business Model Canvas, Startup, Cosmetic, Local Product.